2017
DOI: 10.1016/j.jvs.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of concomitant renal reconstruction during open paravisceral aortic aneurysm repair

Abstract: Renal artery reconstruction at the time of open repair of paravisceral aneurysms is associated with an increased complication rate, primarily driven by occlusion of reimplanted vessels and increased dialysis requirement. As reported by others, nonelective presentation is the greatest determinant of early death or adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
6
0
4
Order By: Relevance
“…Although his kidney function temporarily improved after the operation, his renal function deteriorated again after 3 weeks. A previous study demonstrated that open repair of abdominal aortic aneurysm, including renal artery reconstruction, is associated with the development of complications and requirement of dialysis [3]. In the current case, his right renal artery had been totally occluded, and his right kidney was deteriorated as well as atrophied.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Although his kidney function temporarily improved after the operation, his renal function deteriorated again after 3 weeks. A previous study demonstrated that open repair of abdominal aortic aneurysm, including renal artery reconstruction, is associated with the development of complications and requirement of dialysis [3]. In the current case, his right renal artery had been totally occluded, and his right kidney was deteriorated as well as atrophied.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the clinical characteristics and etiology of CRA may be different from common atherosclerotic diseases. The detailed mechanisms of the development of CRA remain uncertain [1, 2, 3, 4]. A previous study investigated serum calcification markers and aortic tissue in patients with CRA [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparable series, in which 76 renal arteries were revascularised, Wooster et al 13 reported a 9.6% rate of renal loss at 18 months, most of them related to renal artery re-implantation with renal artery endarterectomy, with only four bypasses performed. It is believed that the better results of the present study can be attributed to avoidance of renal artery endarterectomy and the preferential use of a bypass to a healthy renal artery.…”
Section: Discussionmentioning
confidence: 98%
“…We rejected that option because aortic surgery and renal reimplantation are associated with substantial rates of complications. 5 The second option was a hybrid treatment including direct surgical reimplantation of the ectopic renal artery or a prosthetic bypass from the left external iliac artery to the ectopic renal artery, both with an extraanatomic approach, followed by EVAR as an immediate or delayed treatment. However, we believe that the passage of the endoprosthesis shaft into a shaggy iliac axis may have led to left renal embolism.…”
Section: Discussionmentioning
confidence: 99%